Role Conflict and Coping Behaviour of Married Working Women - Ahmad, Aminah (Universiti Putra Malaysia Press, 1995)
This study examined the conflict that married women experienced between work and family roles, and analysed the coping behaviour. Data from 82 professional women from six research institutes revealed that married women experienced work-family conflict with varying intensities in trying to meet the expectations of work and family roles. In managing the work-family conflict, the women tended to cope through reactive role behaviour, and personal role redefinition by changing their own attitudes and perceptions of role expectations. These two strategies were more frequently adopted than structural role redefinition, which entails changing the expectation of members in the role set such as family members, colleagues and leaders at the work place, and society. Implications of these findings for working women and suggestions for further research are discussed.